(untitled) (The Research of Medical Science Review, 2025)
OBJECTIVE: To evaluate the etiology and outcomes in AKI patients admitted in intensive care unit at Indus Hospital Karachi. METHODOLOGY: This study was conducted at Indus Hospital, Karachi, it included 18–70 years old patients presented with acute kidney injury in Intensive Care Unit (ICU). The etiological factors evaluated encompassed sepsis, hypovolemic shock, and traumatic injuries. The patient cohort was monitored for various outcomes, including the necessity for dialysis, extended duration of ICU admission, and mortality rates. The data underwent statistical analysis utilizing SPSS software version 26, with a significance threshold established at p ≤ 0.05. RESULTS: Among 250 AKI patients (mean age 53.08 ± 14.97 years; 54.4% male), sepsis was the most common (41.2%), followed by hypovolemic shock (12.8%) and trauma (1.6%). Hemodialysis was required in 30.4%, remained for a longer period in ICU was 36.8%, and in-hospital mortality was 14.4%. There were significant gender differences for all outcomes (p <0.05). CONCLUSION: This study demonstrated that acute kidney injury in ICU patients is mainly caused by sepsis in a tertiary hospital. Marked disparities attributable to gender were observed concerning the necessity for dialysis, the duration of ICU hospitalization, and in-hospital mortality rates. The prompt recognition and intervention of sepsis-induced acute kidney injury are imperative to enhance clinical outcomes, particularly in critical care environments characterized by limited resources.